Developing one’s own language: a narrative of Arabic acquisition during mobility from West Africa to Europe via Libya - (:unkn) unknown (My University, 2023)
In the course of transnational, irregular, stepwise mobilities between West Africa, North Africa and Western Europe, many migrants develop communicative practices of Arabic. Within the framework of the sociolinguistics of mobility and using a biographical approach, this paper examines a narrative of Arabic acquisition and use along a seven-year journey from Niger through Libya, Malta, and then France. It aims to provide first-person insights into the sociolinguistic dynamics and factors that influence language practice during mobility. The first part situates the narrative within the Libyan sociopolitical context and migratory landscape and underlines the social diversity of mobility networks, drawing on other collected narratives and observations. The narrative describes a multi-situated acquisition and exposure to different varieties and norms of Arabic through interactions with mobile speakers and engagement with digital media. Through an analysis of the narrator’s Arabic speech form, the study highlights the heterogeneity of his linguistic repertoire, the fluidity of his language use, and the processes of reappropriation and accommodation. It also explores the relationship between the speaker’s repertoire and his emotional experiences as expressed through his discourse on Arabic and its varieties. Ultimately, this paper argues that the speaker has developed a unique use and perception of Arabic that reflects his personal, geographical, and social trajectory, as well as his feelings of affiliations/non-affiliations.
Keywords: African Research